2022
DOI: 10.1155/2022/8322029
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic Performance Analysis of STEP System in Internet of Vehicles Based on Queuing Theory

Abstract: The Internet of vehicles (IoV) is an important research area of the intelligent transportation systems using Internet of things theory. The complex event processing technology is a basic issue for processing the data stream in IoV. In recent years, many researchers process the temporal and spatial data flow by complex event processing technology. Spatial Temporal Event Processing (STEP) is a complex event query language focusing on the temporal and spatial data flow in Internet of vehicles. There are four proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Queuing theory has a unique advantage in studying system performance because it reduces the complexity of the problem and facilitates research. In reference [12], spatial-temporal event processing (STEP) was used to process spatiotemporal data streams for the IoV, and a queuing network model was utilized to evaluate the response time of the STEP temporal stream processing system. In reference [13], the authors modeled the cloud computing system as an M/G/1 queue and proposed a task scheduling algorithm based on similar tasks to reduce energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…Queuing theory has a unique advantage in studying system performance because it reduces the complexity of the problem and facilitates research. In reference [12], spatial-temporal event processing (STEP) was used to process spatiotemporal data streams for the IoV, and a queuing network model was utilized to evaluate the response time of the STEP temporal stream processing system. In reference [13], the authors modeled the cloud computing system as an M/G/1 queue and proposed a task scheduling algorithm based on similar tasks to reduce energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…Resource scheduling in IOV is mainly conducted through vehicle to vehicle (V2V) and vehicle to RSU (V2R). However, since V2V communication and V2R communication do not encrypt data, malicious nodes can intercept or even tamper with communication data in the process of data transmission [17]. On the other hand, the information between entities participating in resource scheduling is opaque, RSUs located on the roadside are vulnerable to external attacks, and there is a lack of an effective trust mechanism between entities participating in resource scheduling.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%